Manifestation of Surrealism in Charlotte Perkins Gilman’s Short Story The Yellow Wallpaper - Muhajir, Fatimah; Nugroho, Bayu Aji (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
ABSTRACT This study examines the elements of surrealism in literary works, focusing on how authors employ realist techniques to explore subconscious realities and create complex meanings. The research uses a descriptive-qualitative method by describing data such as dialogues, narratives, or quotations, which are then processed through elaboration and analysis. This study applies surrealist literary theory, primarily referring to the ideas of André Breton as a central figure in the surrealist movement, combined with Sigmund Freud’s psychological theory. The object of analysis is a short story titled "The Yellow Wallpaper" by American feminist writer Charlotte Perkins Gilman. This short story was selected for its strong surrealist representation. The findings show that the work contains typical characteristics of surrealism, such as the blending of reality and imagination, representations of dreams, myths, fantasy, unusual symbolism, absurdity, and irrationality as the main narrative elements. Through these surrealist techniques, the author conveys implicit social and psychological critiques through the depiction of an anonymous narrator character. Thus, this study affirms that surrealism in literature is not merely an aesthetic and imaginative style, but also serves as a medium for exploring the psyche and alternative realities. Key words: surrealism, automatism, myth, fantasy, metamorphosis, short story The Yellow-Wallpaper.